Posterior Revision of Lumbar Interbody Fusion Cages Migration: Clinical Case Series and Literature Review - Ayman Galhom (Egyptian Spine Association, 2017)
Background Data: Revision surgery for lumbar interbody cage migration is technically demanding.Cage related complication may lead to failure of fusion. Revision of such morbidity is associated with increased risk of permanent neurological insult. Purpose: To analyze the efficacy of posterior approach and iliac crest auto grafting technique in revision of migrated intervertebral cages. Study Design: Retrospective descriptive clinical case study. Patients and Methods: From January 2010 to January 2016, we operated 106 patients underwent posterior lumbar interbody fusion (PLIF) with single cage application per level for treatment of degenerative spondylolisthesis. Of these, 12 patients experiencing cage subsidence and retropulsion. In subsidence, it was graded from 0 to III. Retropulsion was considered if the cage beyond the level of the posterior longitudinal line of the index two vertebrae. Patients were assessed pre-operatively for pain and clinical functional outcome by visual analogue scale (VAS) and Oswestry disability index (ODI), respectively. Patient with VAS score ≥5; at least 20% deterioration on ODI or with the superadded neurological deficit was considered candidates for revision surgery. Results: Cage migration incidence was 11.3%, with subsidence (6.7%), and retropulsion (4.6%) of all patients. The average time for subsidence was 3.3 months (range 2 to 6 months). Five patients with grade-II and III subsidence underwent revision surgery for foraminal decompression, augmenting fixation and adding postero-lateral iliac crest bone graft. Retropulsion was encountered in 4 patients and all needed revision surgery for cage retrieval and redo fusion. Grade-I subsidence could be treated conservatively. All surgically treated patients had a good result in VAS and ODI after a second surgery which maintained during follow up with P<0.05. Conclusion: Migration of posterior lumbar interbody fusion cage into the endplates or spinal canal is usually associated with patient dissatisfaction. Revision surgery indicated for cage retropulsion or high-grade subsidence. The posterior approach is technically demanding, safe, and effective for cage migration revision surgery. (2017ESJ141)